2022
DOI: 10.1107/s2052252522005577
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relations of a unique and systematic dataset of 19 isostructural multicomponent apremilast forms

Abstract: The structure–property relations are examined for apremilast cocrystals and solvates in this work. A unique and large dataset of multicomponent crystal forms is presented including 7 cocrystals and 12 solvates. In total, 15 of the presented multicomponent forms and their crystal structures are published here for the first time. This dataset is unique owing to the extreme crystal packing similarity of all 19 crystal forms. This fact makes the evaluation of structure–property relations significantly easier and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Likewise, for solvates in which solvent is mainly a void filler, the packing efficiency is not always higher than that in the nonsolvated form, and the solvent size, shape, and the intermolecular interactions often determine the solvent selectivity . In contrast, if the solvent is situated in large structure voids, it can have almost no effect on the structure of the host framework, and the properties or the size of the solvent can have minimal to no role in discrimination of what solvents can be included in the structure, as, for example, observed for the clathrates of deoxycholic, cholic, and apocholic acids. , Detailed studies of the highly similar solvates of 3,5 dihydroxybenzoic acid and apremilast solvates and cocrystals, however, have shown that differences in the host framework present in different phases can be identified and linked with the properties of the solvent (or coformer).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, for solvates in which solvent is mainly a void filler, the packing efficiency is not always higher than that in the nonsolvated form, and the solvent size, shape, and the intermolecular interactions often determine the solvent selectivity . In contrast, if the solvent is situated in large structure voids, it can have almost no effect on the structure of the host framework, and the properties or the size of the solvent can have minimal to no role in discrimination of what solvents can be included in the structure, as, for example, observed for the clathrates of deoxycholic, cholic, and apocholic acids. , Detailed studies of the highly similar solvates of 3,5 dihydroxybenzoic acid and apremilast solvates and cocrystals, however, have shown that differences in the host framework present in different phases can be identified and linked with the properties of the solvent (or coformer).…”
Section: Introductionmentioning
confidence: 99%